Diversity and spatial distribution patterns of the soft-bottom macrofauna communities on the Portuguese continental shelf - Martins, R. (2018)
This study presents a comprehensive assessment of the diversity and spatial distribution of the soft-bottom benthic macrofauna communities along the Portuguese continental shelf and discusses the relationship between biological and environmental data. A total of 145 sites were sampled using a 0.1m2Smith-McIntyre grab covering the whole west and south coast of Portugal, at depths ranging 13 and 195m. More than 30,000 specimens were identified corresponding to 737 taxa, mostly annelids (43% of the total taxa). The most frequent species were Ampharete finmarchica, Ampelisca sp. and Lumbrineris lusitanica while the most abundant were Mediomastus fragilis, Polygordius appendiculatus and Ampharete finmarchica. Abundance ranged between 7 and 1307 specimens per 0.1m2and alpha diversity reached a maximum of 96 taxa per 0.1m2. Gravel sediments, and shallow and sheltered areas presented higher diversity values than mud sediments and deeper sites. Six major benthic assemblages were identified: (a) Coarse sediments, mostly located on the western shelf, with Protodorvillea kefersteini, Pisione remota, Angulus pygmaeus and several other interstitial species; (b) near shore fine sands with Magelona johnstoni, Urothoe pulchella and Angulus fabula; (c) Abra alba community in northwestern deep muddy sands; (d) Southwestern very deep muddy sands characterized by Galathowenia oculata, Lumbrinerides amoureuxi and other burrowers and tubicolous polychaetes; (e) Euchone rubrocincta, Nematonereis unicornis and other warmer water species in muddy sands of the southern and sheltered shelf; and (f) muds dominated by Sternaspis scutata, Heteromastus filiformis and Psammogammarus caecus. Sediment grain-size, organic matter, depth and hydrodynamic regime were the variables best related to the macrofauna distribution patterns, highlighting the transitional characteristics of this northeastern Atlantic area, where northern and subtropical faunas can coexist.